1996
DOI: 10.1093/protein/9.8.631
|View full text |Cite
|
Sign up to set email alerts
|

The subunit structure of human macrophage migration inhibitory factor: evidence for a trimer

Abstract: The subunit structure of human macrophage migration inhibitory factor (MIF) has been studied by preliminary X-ray analysis of wild-type and selenomethionine-MIF and dynamic light scattering. Crystal form I of MIF belongs to space group P2(1)2(1)2(1) and is grown from 2 M ammonium sulfate at pH 8.5. A native data set has been collected to 2.4 A resolution. Self-rotation studies and Van values indicate that three molecules per asymmetric unit are present. A data set to 2.8 A resolution has been collected for cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 0 publications
1
54
0
2
Order By: Relevance
“…The human MIF was prepared as previously described (17). For NMR experiments, minimal media that contained 15 NH 4 Cl (Cambridge Isotope Laboratories, Inc.) was used as the nitrogen source to express 15 N-rhMIF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human MIF was prepared as previously described (17). For NMR experiments, minimal media that contained 15 NH 4 Cl (Cambridge Isotope Laboratories, Inc.) was used as the nitrogen source to express 15 N-rhMIF.…”
Section: Methodsmentioning
confidence: 99%
“…Once released, MIF activates the receptor CD74 in a complex with CD44 (13), or the chemokine receptors CXCR2 (14) and CXCR4 (15), initiating a cascade of intracellular signaling (16). One aspect of MIF that remains enigmatic is the presence of a catalytic site, highly conserved among all MIFs and present between subunits of the trimer (16)(17)(18)(19). No physiologic substrate for MIF has been identified, but "pseudosubstrates" have been found that allow for screening inhibitors at this site (20,21).…”
mentioning
confidence: 99%
“…Nevertheless, the uniqueness of an enzymatic activity associated with a cytokine led to studies elucidating the structure-activity relationship between the two activities. These studies revealed that in vitro, MIF exists as a 37.5-kDa homotrimer (26,27). The three monomers that form the trimer exist as a ␤-␣-␤ structure composed of two anti-parallel ␣-helices packed against a fourstranded ␤-sheet.…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%
“…Each monomer consists of 114 amino acid residues and has a molecular weight of 12,343 Da. As revealed by X-ray crystallography [19,20], the tertiary structure of MIF defines a novel protein fold, which is characterized by the packing of an extended 4-stranded b-sheet and two antiparallel a-helices (Fig. 1A).…”
mentioning
confidence: 99%
“…1B). Although MIF crystallizes as a trimer [19], experimental studies employing NMR spectroscopy [21], size-exclusion chromatography [22], chemical cross-linking [23,24], and analytical ultracentrifugation support the existence of dimeric and monomeric forms in solution [24].…”
mentioning
confidence: 99%